CD83 expression is essential for Treg cell differentiation and stability - Döbbeler, Marina; Koenig, Christina; Krzyzak, Lena; Seitz, Christine; Wild, Andreas; Ulas, Thomas; Bassler, Kevin; Kopelyanskiy, Dmitry; Butterhof, Alina; Kuhnt, Christine; Kreiser, Simon; Stich, Lena; et al. (JCI Insight, 2018)
Foxp3-positive regulatory T cells (Tregs) are crucial for the maintenance of immune homeostasis and keep immune responses in check. Upon activation, Tregs are transferred into an effector state expressing transcripts essential for their suppressive activity, migration, and survival. However, it is not completely understood how different intrinsic and environmental factors control differentiation. Here, we present for the first time to our knowledge data suggesting that Treg-intrinsic expression of CD83 is essential for Treg differentiation upon activation. Interestingly, mice with Treg-intrinsic CD83 deficiency are characterized by a proinflammatory phenotype. Furthermore, the loss of CD83 expression by Tregs leads to the downregulation of Treg-specific differentiation markers and the induction of an inflammatory profile. In addition, Treg-specific conditional knockout mice showed aggravated autoimmunity and an impaired resolution of inflammation. Altogether, our results show that CD83 expression in Tregs is an essential factor for the development and function of effector Tregs upon activation. Since Tregs play a crucial role in the maintenance of immune tolerance and thus prevention of autoimmune disorders, our findings are also clinically relevant.
EVALuna2:36212

FAM13A is associated with non-small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival - Eisenhut, Felix; Heim, Lisanne; Trump, Sonja; Mittler, Susanne; Sopel, Nina; Andreev, Katerina; Ferrazzi, Fulvia; Ekici, Arif Bülent; Rieker, Ralf; Springel, Rebekka; Assmann, Vera Elisabeth; Lechmann, Matthias; et al. (OncoImmunology, 2017)
Genome-wide association studies (GWAS) associated Family with sequence similarity 13, member A (FAM13A) with non-small cell lung cancer (NSCLC) occurrence. Here, we found increased numbers of FAM13A protein expressing cells in the tumoral region of lung tissues from a cohort of patients with NSCLC. Moreover, FAM13A inversely correlated with CTLA4 but directly correlated with HIF1? levels in the control region of these patients. Consistently, FAM13A RhoGAP was found to be associated with T cell effector molecules like HIF1? and Tbet and was downregulated in immunosuppressive CD4(+)CD25(+)Foxp3(+)CTLA4(+) T cells. TGF?, a tumor suppressor factor, as well as siRNA to FAM13A, suppressed both isoforms of FAM13A and inhibited tumor cell proliferation. RNA-Seq analysis confirmed this finding. Moreover, siRNA to FAM13A induced TGF? levels. Finally, in experimental tumor cell migration, FAM13A was induced and TGF? accelerated this process by inducing cell migration, HIF1?, and the FAM13A RhoGAP isoform. Furthermore, siRNA to FAM13A inhibited tumor cell proliferation and induced cell migration without affecting HIF1?. In conclusion, FAM13A is involved in tumor cell proliferation and downstream of TGF? and HIF1?, FAM13A RhoGAP is associated with Th1 gene expression and lung tumor cell migration. These findings identify FAM13A as key regulator of NSCLC growth and progression.
EVALuna2:6835

Murine CD83-positive T cells mediate suppressor functions in vitro and in vivo - Kreiser, Simon; Eckhardt, Jenny; Kuhnt, Christine; Stein, Marcello F.; Krzyzak, Lena; Seitz, Christine; Tucher, Christine; Knippertz, Ilka; Becker, Christoph; Günther, Claudia; Steinkasserer, Alexander; Lechmann, Matthias (Immunobiology, 2015)
The CD83 molecule (CD83) is a well-known surface marker present on mature dendritic cells (mDC). In this study, we show that CD83 is also expressed on a subset of T cells which mediate regulatory T cell (Treg)-like suppressor functions in vitro and in vivo. Treg-associated molecules including CD25, cytotoxic T lymphocyte antigen-4 (CTLA-4), glucocorticoid-induced TNFR family-related gene (GITR), Helios and neuropilin-1 (NRP-1) as well as forkhead box protein 3 (FOXP3) were specifically expressed by these CD83(+) T cells. In contrast, CD83(-) T cells showed a naive T cell phenotype with effector T cell properties upon activation. Noteworthy, CD83(-) T cells were not able to upregulate CD83 despite activation. Furthermore, CD83(+) T cells suppressed the proliferation and inflammatory cytokine release of CD83(-) T cells in vitro. Strikingly, stimulated CD83(+) T cells released soluble CD83 (sCD83), which has been reported to possess immunosuppressive properties. In vivo, using the murine transfer colitis model we could show that CD83(+) T cells were able to suppress colitis symptoms while CD83(-) T cells possessed effector functions. In addition, this CD83 expression is also conserved on expanded human Treg. Thus, from these studies we conclude that CD83(+) T cells share important features with regulatory T cells, identifying CD83 as a novel lineage marker to discriminate between different T cell populations.
EVALuna2:1841

Opposing functions of thymic stromal lymphopoietin-responsive basophils and dendritic cells in a mouse model of atopic dermatitis - Schwartz, Christian; Eberle, Jörg; Hoyler, Thomas; Diefenbach, Andreas; Lechmann, Matthias; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:25878

Soluble CD83 ameliorates experimental colitis in mice - Eckhardt, Jenny; Kreiser, Simon; Döbbeler, Marina; Nicolette, C.; Debenedette, M. A.; Tcherepanova, I. Y.; Ostalecki, Christian; Pommer, A. J.; Becker, Christoph; Günther, Claudia; Zinser, E.; Mak, T. W.; et al. (Mucosal Immunology, 2014)
The physiological balance between pro- and anti-inflammatory processes is dysregulated in inflammatory bowel diseases (IBD) as in Crohn's disease and ulcerative colitis. Conventional therapy uses anti-inflammatory and immunosuppressive corticosteroids to treat acute-phase symptoms. However, low remission rate and strong side effects of these therapies are not satisfying. Thus, there is a high medical need for new therapeutic strategies. Soluble CD83, the extracellular domain of the transmembrane CD83 molecule, has been reported to have interesting therapeutic and immunosuppressive properties by suppressing dendritic cell (DC)-mediated T-cell activation and inducing tolerogenic DCs. However, the expression and function of CD83 in IBD is still unknown. Here, we show that CD83 expression is upregulated by different leukocyte populations in a chemical-induced murine colitis model. Furthermore, in this study the potential of sCD83 to modulate colitis using an experimental murine colitis model was investigated. Strikingly, sCD83 ameliorated the clinical disease symptoms, drastically reduced mortality, and strongly decreased inflammatory cytokine expression in mesenteric lymph nodes and colon. The infiltration of macrophages and granulocytes into colonic tissues was vigorously inhibited. Mechanistically, we could show that sCD83-induced expression of indolamine 2,3-dioxygenase is essential for its protective effects.
EVALuna2:1840

Soluble CD83 inhibits skin inflammation to chemical sensitizers - Mihatsch, P.; Boyd, P.; Krzyzak, Lena; Lechmann, Matthias; Nicolas, J.; Mahler, Vera; Steinkasserer, Alexander; Vocanson, Marc (2016)
EVALuna2:26037

The CD83 Molecule – An Important Immune Checkpoint - Grosche, Linda; Knippertz, Ilka; König, Christina; Royzman, Dmytro; Wild, Andreas; Zinser, Elisabeth; Sticht, Heinrich; Muller, Yves; Steinkasserer, Alexander; Lechmann, Matthias (Frontiers in Immunology, 2020)
The CD83 molecule has been identified to be expressed on numerous activated immune cells, including B and T lymphocytes, monocytes, dendritic cells, microglia, and neutrophils. Both isoforms of CD83, the membrane-bound as well as its soluble form are topic of intensive research investigations. Several studies revealed that CD83 is not a typical co-stimulatory molecule, but rather plays a critical role in controlling and resolving immune responses. Moreover, CD83 is an essential factor during the differentiation of T and B lymphocytes, and the development and maintenance of tolerance. The identification of its interaction partners as well as signaling pathways have been an enigma for the last decades. Here, we report the latest data on the expression, structure, and the signaling partners of CD83. In addition, we review the regulatory functions of CD83, including its striking modulatory potential to maintain the balance between tolerance versus inflammation during homeostasis or pathologies. These immunomodulatory properties of CD83 emphasize its exceptional therapeutic potential, which has been documented in specific preclinical disease models.
CRIS-Team Scopus Importer:2020-05-08
Keywords: autoimmunity; CD83; immune tolerance; Treg cells; viral escape mechanism

Thymic stromal lymphopoietin deficiency attenuates experimental autoimmune encephalomyelitis - Eckhardt, J.; Döbbeler, Marina; Koenig, C.; Kuczera, K.; Kuhnt, C.; Ostalecki, C.; Zinser, E.; Mak, T. W.; Steinkasserer, Alexander; Lechmann, Matthias (Clinical and Experimental Immunology, 2015)
In the present study we examined the role of thymic stromal lymphopoietin (TSLP) in experimental autoimmune encephalomyelitis (EAE). Here, we report that TSLP knock-out (KO) mice display a delayed onset of disease and an attenuated form of EAE. This delayed onset was accompanied by a reduced number of encephalitogenic T helper type 1 (Th1) cells in the central nervous system (CNS) of TSLP KO mice. In addition, CD4(+) and CD8(+) T cells from CNS of TSLP KO mice show a reduced activation status in comparison to wild-type mice. It is noteworthy that we could also show that lymph node cells from TSLP KO mice expanded less efficiently and that interleukin (IL)-6-, interferon (IFN)-? and tumour necrosis factor (TNF)-? levels were reduced. Furthermore, CD3(+) T cells isolated in the preclinical phase from myelin oligodendrocyte glycoprotein peptide 35-55 (MOG(35-55))-immunized TSLP KO mice showed a reduced response after secondary exposure to MOG(35-55), indicating that differentiation of naive T cells into MOG(35-55)-specific effector and memory T cells was impaired in KO mice. The addition of recombinant TSLP enhanced T cell proliferation during MOG(35-55) restimulation, showing that T cells also respond directly to TSLP. In summary, these data demonstrate that expression of, and immune activation by, TSLP contributes significantly to the immunopathology of EAE.
EVALuna2:19524

Topical application of soluble CD83 induces IDO-mediated immune modulation, increases Foxp3+ T cells, and prolongs allogeneic corneal graft survival - Bock, Felix; Roessner, Susanne; Onderka, Jasmine; Lechmann, Matthias; Pallotta, Maria Teresa; Fallarino, Francesca; Boon, Louis; Nicolette, Charles; Debenedette, Mark A.; Tcherepanova, Irina Y.; Grohmann, Ursula; Steinkasserer, Alexander; et al. (Journal of Immunology, 2013)
Modulation of immune responses is one of the main research aims in transplant immunology. In this study, we investigate the local immunomodulatory properties of soluble CD83 (sCD83) at the graft-host interface using the high-risk corneal transplantation model. In this model, which mimics the inflammatory status and the preexisting vascularization of high-risk patients undergoing corneal transplantation, allogeneic donor corneas are transplanted onto sCD83-treated recipient animals. This model allows the direct and precise application of the immune modulator at the transplantation side. Interestingly, sCD83 was able to prolong graft survival after systemic application as well as after topical application, which is therapeutically more relevant. The therapeutic effect was accompanied by an increase in the frequency of regulatory T cells and was mediated by the immune-regulatory enzyme IDO and TGF-?. In vitro, sCD83 induced long-term IDO expression in both conventional and plasmacytoid dendritic cells via autocrine or paracrine production of TGF-?, a cytokine previously shown to be an essential mediator of IDO-dependent, long-term tolerance. These findings open new treatment avenues for local immune modulation after organ and tissue transplantation.
EVALuna2:21223